A Degenerate Peptide Library Approach to Reveal Sequence Determinants of Methyllysine-Driven Protein Interactions - Kupai, Ariana; Vaughan, Robert M.; Dickson, Bradley M.; Rothbart, Scott B. (Frontiers in Cell and Developmental Biology, 2020)
Lysine methylation facilitates protein-protein interactions through the activity of methyllysine (Kme) “reader” proteins. Functions of Kme readers have historically been studied in the context of histone interactions, where readers aid in chromatin-templated processes such as transcription, DNA replication and repair. However, there is growing evidence that Kme readers also function through interactions with non-histone proteins. To facilitate expanded study of Kme reader activities, we developed a high-throughput binding assay to reveal the sequence determinants of Kme-driven protein interactions. The assay queries a degenerate methylated lysine-oriented peptide library (Kme-OPL) to identify the key residues that modulate reader binding. The assay recapitulated methyl order and amino acid sequence preferences associated with histone Kme readers. The assay also revealed methylated sequences that bound Kme readers with higher affinity than histones. Proteome-wide scoring was applied to assay results to help prioritize future study of Kme reader interactions. The platform was also used to design sequences that directed specificity among closely related reader domains, an application which may have utility in the development of peptidomimetic inhibitors. Furthermore, we used the platform to identify binding determinants of site-specific histone Kme antibodies and surprisingly revealed that only a few amino acids drove epitope recognition. Collectively, these studies introduce and validate a rapid, unbiased, and high-throughput binding assay for Kme readers, and we envision its use as a resource for expanding the study of Kme-driven protein interactions.